2019
DOI: 10.1101/671529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histopathological Study Of Different Organs Of Charles Foster Rats Under The Exposure Of Pueraria tuberosa

Abstract: Objective: The present study was undertaken to investigate the safe doses of Pueraria tuberosa water extract (PTWE) on different organs .Methodology: Haematoxylin and eosin staining was used to study the morphological alterations in heart, intestine, testis, adrenal gland and spleen. Followed the OECD guidelines 407 of repeated toxicity with respect to the selection of dose and days for different organs. The selected doses of PTWE were 250, 500, 1000 and 2000 mg/kg bw and the durations selected were 7, 14, 21 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Aqueous tuber extract of the plant showed an elevated expression of nephrin and SOD and a declined expression of cysteinyl aspartate specific proteinase 3 (caspase-3), interleukin 6 (IL-6), nuclear factor kappa B (NF-κB), protein kinase C epsilon type (PKCε), tumor necrosis factor alpha (TNF-α), vascular endothelial growth factor (VEGF), matrix metalloproteinase-9 (MMP-9), and hypoxia-inducible factor 1-alpha in STZ-induced diabetic rats ( Srivastava et al, 2019 ). In another experiment, it has been shown that administration of P. tuberosa water extract in alloxan-induced rat diabetic model resulted in decrease in SGOT (serum glutamic oxaloacetic transaminase), SGPT (serum glutamic pyruvic transaminase), and alkaline phosphates level and improved deformed hepatocytes and significant decrease in blood glucose levels as well as apoptosis ( Pandey et al, 2019 ). The tuber extract contains different bioactive compounds that may act as agonists on glucagon-like peptide-1 hormone released from intestine and can also protect β-cells of the pancreas.…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous tuber extract of the plant showed an elevated expression of nephrin and SOD and a declined expression of cysteinyl aspartate specific proteinase 3 (caspase-3), interleukin 6 (IL-6), nuclear factor kappa B (NF-κB), protein kinase C epsilon type (PKCε), tumor necrosis factor alpha (TNF-α), vascular endothelial growth factor (VEGF), matrix metalloproteinase-9 (MMP-9), and hypoxia-inducible factor 1-alpha in STZ-induced diabetic rats ( Srivastava et al, 2019 ). In another experiment, it has been shown that administration of P. tuberosa water extract in alloxan-induced rat diabetic model resulted in decrease in SGOT (serum glutamic oxaloacetic transaminase), SGPT (serum glutamic pyruvic transaminase), and alkaline phosphates level and improved deformed hepatocytes and significant decrease in blood glucose levels as well as apoptosis ( Pandey et al, 2019 ). The tuber extract contains different bioactive compounds that may act as agonists on glucagon-like peptide-1 hormone released from intestine and can also protect β-cells of the pancreas.…”
Section: Methodsmentioning
confidence: 99%